2011
DOI: 10.3928/00220124-20110324-05
|View full text |Cite
|
Sign up to set email alerts
|

Support Programs for New Graduates in Pediatric Nursing

Abstract: This study examined intent to stay and the relationship between work satisfaction and burnout in a sample of new registered nurse graduates hired at a freestanding children's hospital. The following research questions were addressed: (1) Two years after initial employment, what is the percentage of new graduates who intend to stay on the job? (2) Is there a relationship between work satisfaction and burnout? (3) What is the turnover rate after the implementation of a support group program for new registered nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
35
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 84 publications
2
35
0
Order By: Relevance
“…Nurse burnout has been associated with cost-reduction measures that result in shorter stays for patients and a greater nursing-intensity (Kanai-Pak et al, 2008). Messmer et al, (2010) found that allocating resources to support new nursing graduates improves retention and prevents burnout, and recommended that structured orientation programmes be continued despite current economic constraints to integrate nurse graduates into the nursing workforce.…”
Section: Resultsmentioning
confidence: 99%
“…Nurse burnout has been associated with cost-reduction measures that result in shorter stays for patients and a greater nursing-intensity (Kanai-Pak et al, 2008). Messmer et al, (2010) found that allocating resources to support new nursing graduates improves retention and prevents burnout, and recommended that structured orientation programmes be continued despite current economic constraints to integrate nurse graduates into the nursing workforce.…”
Section: Resultsmentioning
confidence: 99%
“…The context includes both the physical and social environments within which nurses are trained and practice after graduation. To compensate for preparation limitations, most nursing bodies require that graduates undergo a transitory program before licensure, such as nurse residency or internship programs [13,29] preparing the nurse before leaving the nest [21] . Graduate programs, such as preceptorship [2,22] and remunerated community service [30] which are designed to socialize graduates into their new roles and environments, could be valuable for professional maturity and patient safety [31] .…”
Section: Discussionmentioning
confidence: 99%
“…The pediatric nurses working in certain specialty areas, such as the critical care unit or hematology/oncology unit are thought to be more susceptible to burnout. The pediatric oncology nurses reported to have significantly lower level of personal accomplishment in burnout scale compared to adult oncology nurses and one-third of nurses in neonatal intensive care unit reported symptoms of burnout [17][18][19] .…”
mentioning
confidence: 99%
“…After an implementation of nursing support program, the turnover rate among new pediatric nurses declined [19] . The pediatric critical care nurses who perceived themselves as well-prepared and had the ability to care for dying patients reported higher compassion satisfaction and lower burnout [20] .…”
mentioning
confidence: 99%